Про естетику хорору - Дараган, Д. (ХНУРЕ, 2021)
The quite ambiguous theme of horror has embarrass artists for centuries and has many connoisseurs. Today, the aesthetics of horror is gaining more and more importance in an attempt to answer questions about the nature of horror, its psychological essence and the reasons for its popularity. Cause of horror, people overcome their fears and at the same time satisfy their thirst for knowledge. Perhaps by overcoming the fear of the unknown, we try to overcome xenophobia in various manifestations of life and at the same time the fear of death.
Keywords: філософія; естетика хорору